A atuação do profissional de Relações Públicas na área de gestão de pessoas: análise do projeto "Embaixadores do clima" - Araújo, Juliana Conceição [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This study aims to provoke a reflection on how the Public Relations professional in the area of People Management carried out based on the project “Embaixadores do Clima”. In this context, the theme "The employee's well-being" becomes increasingly important and discussed, it will be constantly presented and it will serve as a crucial point for this study, considering that the project mentioned above has as the main objective to provide an environment of better experiences for the employee. For this, two methodologies will be used, the first one is Bibliographic Research in order to generate a basis with relevant themes for this study such as World of Work, Organizational Climate and People Management and finally, Research-action considering that the mentioned project was experienced by the researcher and it will be a way for her to reflect on the results. In synthesis, this project brought significant improvements to the organization, demonstrating that it achieved its objective of improving the organizational climate and internal communication of the members of the company. However, as it is a recent project, it presents the need for specific improvements for the next groups.

Este estudo objetiva uma reflexão sobre a maneira a qual o profissional de Relações Públicas atua na área de Gestão de Pessoas, realizado a partir do projeto “Embaixadores do Clima”. Neste contexto, o bem estar do colaborador torna-se um tema cada vez mais importante e discutido e, por isso, será constantemente apresentado e servirá como ponto crucial para o trabalho, em vista que o projeto citado anteriormente tem como principal objetivo proporcionar um ambiente de melhores vivências para o colaborador. Para isso, serão utilizadas duas metodologias, a Pesquisa Bibliográfica, a fim de gerar embasamento sobre temas relevantes para este trabalho, como Mundo do Trabalho, Clima Organizacional e Gestão de Pessoas e, por fim, a Pesquisa-Ação, já que o projeto citado foi vivenciado pela pesquisadora e será um espaço para que a mesma reflita sobre os resultados do mesmo. Em síntese, o projeto trouxe melhorias significativas para a organização, demonstrando que o mesmo atingiu o seu objetivo de aperfeiçoar o clima organizacional e comunicação interna da empresa.
The role of the Public Relations professional in the area of ​​people management: analysis of the "Climate Ambassadors" project
Keywords: Public relations; Personnel administration; Organizational climate; Relações públicas; Administração de pessoal; Clima organizacional; Empregados; Employee